Experimental and Numerical Investigation of Turbulent Vortex Shedding - Shiri, Hamidreza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Wake structures as well as flow properties formed behind bluff bodies have received great interest among researchers for years. As a result of various application of bluff bodies in different engineering topics and industry, there has been a growing interest on this phenomenon. As a significant feature of these geometries has been the formation of various vortices in the wake, possible suppression of such phenomenon is the desired outcome in order to reduce the fluctuation forces act on the structures in civil engineering application. The Reynolds de-composition is a very common technique to approach these problems. However, some researchers tackle such problems with an alternative technique known as the triple decomposition. Since the flow structure of a bluff body comprises large-scale organized motion, the timevarying component in the wake region of a bluff -body flow consists of a periodic component (coherent structure) that can be distinguished from a random (incoherent) component. In the present study, incoherent turbulent flow structures in the near-wake region downstream of a square cylinder have been studied by employing triple decomposition. It was observed that the main incoherent turbulent kinetic energy production occurs in the region with the same width of square cylinder. Moreover, it was demonstrated that while a vortex is developing from one edge with maximum incoherent streamwise stress, the initiated shear layers from the other edge exhibit a maximum in incoherent transverse stress production. In addition, wake region behind three modified geometries namely Circular Cylinder (CC), Semi Circular Cylinder (SC) and C shape (CS) are investigated experimentally and numerically for Re of 20000 to identify the effects of shape modification on the wake region. These effects have been discussed in regards to flow structure, Turbulent Kinetic Energy (TKE), pressure and vorticity. It was observed that while CC and SC demonstrated almost similar level of TKE peak value with just 6% rising on SC, CS wake region exhibit a significant increase of 40% in the peak value with respect to CC. It was also illustrated that the vorticity in the wake region of SC is mostly concentrated along the edges of separated shear layers.

ÖZ: Değişik şekilli cisimlerin arkasındaki akış özellikleri ve iz yapıları, yıllardır birçok araştırmacıyı büyülemiştir. Değişik şekilli cisimlerin mühendislik ve endüstride çeşitli uygulamalarının bir sonucu olarak, bu olguya artan bir ilgi vardır. Bu cisimlerin önemli bir özelliği, iz bölgesinde girdap sokağı oluşması olduğundan, bu fenomenin olası bastırılması istenen bir sonuçtur. Reynolds ayrıştırması bu problemlere yaklaşmak için çok yaygın bir tekniktir. Bununla birlikte, bazı araştırmacılar, üçlü ayrıştırma olarak bilinen alternatif bir teknikle bu tür sorunları çözmektedir. Bir değişik şekilli cismin gövdesinin akış yapısı büyük ölçekli organize hareket içerdiğinden, bir değişik şekilli cisim akışının iz bölgesindeki zamanla değişen bileşen, rastgele (tutarsız) bir bileşenden ayırt edilebilen periyodik bir bileşenden (tutarlı yapı) oluşur. Bu çalışmada, kare bir silindirin akış aşağısında uyanmaya yakın bölgedeki tutarsız türbülanslı akış yapıları üçlü ayrıştırma kullanılarak incelenmiştir. Ana tutarsız türbülanslı kinetik enerji üretiminin aynı genişlikte kare silindire sahip bölgede meydana geldiği gözlemlendi. Ayrıca, maksimum tutarsız akış yönünde gerilme ile bir kenardan bir girdap gelişirken, diğer kenardan başlatılan kayma katmanlarının tutarsız enine gerilme üretiminde bir maksimum sergiledikleri gösterilmiştir. Ayrıca, şekil değişikliğinin iz bölgesi üzerindeki etkilerini belirlemek için Re=20000 için Dairesel Silindir (CC), Yarı Dairesel Silindir (SC) ve Dairesel Kabuk (S) olmak üzere üç değiştirilmiş geometrinin arkasındaki iz bölgesi deneysel ve sayısal olarak incelenmiştir. Bu etkiler akış yapısı, TKE, basınç ve girdap açısından tartışılmıştır. CC ve SC'nin SC'de sadece %6'lık bir artışla hemen hemen benzer düzeyde TKE tepe değeri gösterdiği gözlenirken, S iz bölgesinin CC'ye göre tepe değerinde %40'lık önemli bir artış gösterdiği gözlemlendi. SC'nin iz bölgesindeki girdaplığın çoğunlukla ayrılmış kesme tabakalarının kenarları boyunca yoğunlaştığı da gösterilmiştir.
Doctor of Philosophy in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2021. Supervisor: Prof. Dr. Hasan Hacışevki
Keywords: Fluid Dynamics; Fluid mechanics; Coherent Flow Structure; Incoherent Flow Structure; Vortex Shedding; Suppression; Square Cylinder; Circular Cylinder (CC); Semi Circular Cylinder (SC); C shape Cylinder (CS)